The significance of coagulase-negative staphylococci bacteremia in a low resource setting - Zaidah Abdul Rahman; Siti Hawa Hamzah; Siti Asma' Hassan; Sabariah Osman; Siti Suraiya Md Noor (Journal of Infection in Developing Countries)
Introduction: Coagulase-negative staphylococci (CoNS) are a group of micro-organisms that are increasingly implicated as a cause of significant infection and the leading cause of bloodstream infection (BSI). One important predictor of true BSI is the isolation of CoNS from multiple blood cultures, presuming that the isolates represent the same species. Thus the objective of this study was to determine the significance of repeated CoNS isolated from blood cultures.